Prolonged Pseudohypoxia Targets Ambra1 mRNA to P-Bodies for Translational Repression. - Somayeh Pourpirali; Cristina Valacca; Paola Merlo; Salvatore Rizza; Silvia D'Amico; Francesco Cecconi (PLoS ONE)
Hypoxia has been associated with several pathological conditions ranging from stroke to cancer. This condition results in the activation of autophagy, a cyto-protective response involving the formation of double-membraned structures, the autophagosomes, in the cytoplasm. In this study, we investigated the cellular mechanisms regulating the autophagy gene Ambra1, after exposure to a hypoxia mimetic, cobalt chloride (CoCl2). We observed that, upon CoCl2 administration, activation of the apoptotic machinery was concomitant with down-regulation of the pro-autophagic factor Ambra1, without affecting transcription. Additionally, co-treating the cells with the caspase inhibitor z-VAD-FMK did not restore Ambra1 protein levels, this implying the involvement of other regulatory mechanisms. Partial re-localization of Ambra1 mRNA to non-translating fractions and cytoplasmic P-bodies was further detected. Thus, in this pseudohypoxic context, Ambra1 mRNA translocation to P-bodies and translational suppression correlated with increased cell death.